Left-Handed-Friendly Education in Indonesia (Perceptions, Barriers, and Efforts to Overcome Problems Experienced by Teachers) - Mardianto Mardianto; Makmur Syukri; Irwan S (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze perceptions, barriers and efforts to overcome the problems of left-handed-friendly education in Indonesia. The study focuses on the policy on left-handed-friendly education in Indonesia. This study used a qualitative approach with descriptive analytical study method. The informants of this study were teachers from 4 different provinces. Collecting data using in-depth interviews, participant observation and documentation studies. Furthermore, data analysis used data reduction techniques, data presentation, and verification to draw a conclusion. The results of this study concluded that there was no specific policy in education that regulates left-handed friendly education. This can be seen from (1) there is no consideration of left-handed friendly facilities at the primary, secondary, and higher education levels, (2) educational institution facilities are not friendly to left-handed students, and (3) there is no anticipation of the obstacles that arise. arise related to facilities that are not left-handed friendly. So far, efforts to implement left-handed-friendly education are still providing relatively longer time than other students. Through this research an implication can be obtained that education in Indonesia has not prepared special learning facilities (infrastructure) for left-handed children, because there is no official policy from the government or internal education providers.